Resonance energy transfer, pH‐induced folded states and the molecular interaction of human serum albumin and icariin. (9th February 2015) - Cheng, Xiao‐Xia; Fan, Xiao‐Yang; Jiang, Feng‐Lei; Liu, Yi.; Lei, Ke‐Lin
Abstract: Icariin is a flavonol glycoside with a wide range of pharmacological and biological activities. The pharmacological and biological functions of flavonoid compounds mainly originate from their binding to proteins. The mode of interaction of icariin with human serum albumin (HSA) has been characterized by fluorescence spectroscopy and far‐ and near‐UV circular dichroism (CD) spectroscopy under different pH conditions. Fluorescence quenching studies showed that the binding affinity of icariin with HSA in the buffer solution at different pH values is: K a (pH 4.5) > K a (pH 3.5) > K a (pH 9.0) > K a (pH 7.0). Red‐edge excitation shift (REES) studies revealed that pH had an obvious effect on the mobility of the tryptophan microenvironment and the addition of icariin made the REES effect more distinct. The static quenching mechanism and number of binding sites ( n ≈ 1) were obtained from fluorescence data at three temperatures (298, 304 and 310 K). Both ∆ H 0 < 0 and ∆Ѕ 0 < 0 suggested that hydrogen bonding and van der Waal's interaction were major driving forces in the binding mechanism, and this was also confirmed by the molecular simulation results. The distance r between the donor (HSA) and the acceptor (icariin) was calculated based on Förster non‐radiation energy transfer theory. We found that pH had little impact on the energy transfer between HSA and icariin. Far‐ and near‐UV CD spectroscopy studies further indicated the influence of pH on the complexation process and the alteration in the protein conformation upon binding. Copyright © 2015 John Wiley & Sons, Ltd.